Distinct Cytokine Patterns Associated With Rheumatoid Arthritis Disease Activity: Pola Sitokin yang Berbeda Terkait Dengan Aktivitas Penyakit Artritis Reumatoid - Mohammed, Zainab Abd (Indonesian Journal on Health Science and Medicine, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease marked by systemic inflammation and joint destruction, driven in part by dysregulated cytokine activity. Specific Background: Pro-inflammatory and anti-inflammatory cytokines are central to RA pathogenesis, yet their potential as reliable predictors of disease activity remains underutilized in routine clinical practice. Knowledge Gap: Traditional RA activity markers lack specificity regarding immune pathways, and the diagnostic value of cytokine profiling, especially in relation to sex-based differences, remains unclear. Aim: This study aimed to evaluate serum levels of IL-6, TNF-α, IL-1β, IL-10, and IFN-γ in RA patients versus healthy controls, and assess their correlation with disease activity. Results: RA patients exhibited significantly elevated IL-6, TNF-α, IL-1β, and IFN-γ, and reduced IL-10 (p<0.001). Cytokine levels positively (or inversely for IL-10) correlated with disease activity, with ROC analysis confirming their diagnostic utility. Novelty: The study highlights gender-specific cytokine variations, notably higher IL-6 and lower IL-10 in females, providing insight into sex-based immunopathology. Implications: These findings support cytokine profiling as a promising tool for RA diagnosis and activity monitoring, and underscore the need for personalized, cytokine-targeted therapeutic strategies.Highlight : Cytokine markers predict RA activity – Elevated IL-6, TNF-α, IL-1β, and IFN-γ correlate with disease severity. IL-10 is a key anti-inflammatory marker – Lower levels are linked to worse RA outcomes. ROC analysis confirms diagnostic value – IL-6 had the highest diagnostic accuracy (AUC = 0.91). Keywords : Rheumatoid Arthritis, Cytokines, IL-6, TNF-α, Biomarkers